GE_GERICHTE C/18034/2012 vom 29. November 2012 - GE Cour de justice (2012)
; MAINLEVÉE(LP) ; DÉCISION ; JURIDICTION ARBITRALE | Sentence arbitrale - Mainlevée défitive | CPC.326.1. LP.80.1. CIA.35. CC.2.2